Allelopathic and bloom-forming picocyanobacteria in a changing world - Śliwińska-Wilczewska S. (2018)
Picocyanobacteria are extremely important organisms in the world’s oceans and freshwater ecosystems. They play an essential role in primary production and their domination in phytoplankton biomass is common in both oligotrophic and eutrophic waters. Their role is expected to become even more relevant with the effect of climate change. However, this group of photoautotrophic organisms still remains insufficiently recognized. Only a few works have focused in detail on the occurrence of massive blooms of picocyanobacteria, their toxicity and allelopathic activity. Filling the gap in our knowledge about the mechanisms involved in the proliferation of these organisms could provide a better understanding of aquatic environments. In this review, we gathered and described recent information about allelopathic activity of picocyanobacteria and occurrence of their massive blooms in many aquatic ecosystems. We also examined the relationships between climate change and representative picocyanobacterial genera from freshwater, brackish and marine ecosystems. This work emphasizes the importance of studying the smallest picoplanktonic fractions of cyanobacteria. © 2018 MDPI. All Rights reserved.